(untitled) (Research, Society and Development, 2022)
Microbial inactivation using only Ultrasound (US) vibrations presents considerable advantages by applying green techniques with non-generation of greenhouse gases, eliminating chemicals, and operating conditions close to environmental conditions. However, industrial effluent treatment systems have been investigated as a microbial inactivation step, using isolated US associated with thermal (T) and manometric (P) microbial inactivation techniques. A stainless-steel bench prototype was built for the present study, operating in continuous mode, with a 2.5 L volume test chamber. The indicator microorganism detected in the effluent of a hospital laundry located in the Agreste region of the state of Pernambuco, Brazil, was the E. coli bacterium. In addition to the isolated US effect, US/T, US/P, and US/T/P combinations were obtained using a central composite design (CCD). The factors used for the CCD were frequency, hydraulic detention time, temperature, and pressure. The results showed that the lethality rate increased with the frequency and time of hydraulic detention but was reduced when increasing temperature from 30°C to 50°C and increasing pressure between 1.0 bar and 1.8 bar. Isolated ultrasonic vibrations, at 120 kHz and with 10-minute HRT, reached an inactivation efficiency of 98%. Such a value was found using the thermomannosonic condition around 40 min. The use of the isolated US vibration technique proved advantageous, mainly due to the efficient inactivation results and potential energy and chemical reductions.